The anti-inflammatory and analgesic properties of prosopis chilenses in rats - MA, Abodola; MF, Lutfi; AO, Bakhiet; AH, Mohamed (International Journal of Health Sciences, 2015)
Background: Prosopis chilensis is used locally in Sudan for inflammatory conditions of joints; however, literature lacks scientific evidence for anti-inflammatory effect of this plant. Aims: To evaluate anti-inflammatory and analgesic effects of prosopis chilenses. Material and Methods: Edema inhibition percent (EI %) and hot plate method were used to evaluate anti-inflammatory and analgesic effects of Prosopis chilenses in Wistar albino rats. Anti-inflammatory and analgesic effects of Prosopis chilenses were compared to indomethacin and acetylsalicylic acid respectively. Results: Ethanolic extract of prosopis chilensis at a dose of 200and 100mg/kg body weight achieved peak EI% (EI% = 96.1%) and (EI% = 94.4%) three and four hours after oral dosing respectively. The maximum EI% for indomethacin was 97.0% and was recorded after 4 hours following oral administration of the drug at a dose of 5 mg/kg body weight. Prosopis chilensis extracts at doses of 100 and 200 mg/kg body weight significantly increased the rats’ response time to hot plate compared to acetylsalicylic acid at a dose rate of 100mg/kg body weight (P<0.05). Conclusion: The current results suggest potential anti-inflammatory and analgesic effects of prosopis chilenses. Relevance of these effects to prosopis chilenses phy-to-constituents was discussed. Keywords: analgesic, anti-inflammatory, prosopis chilenses,